THE INFLUENCE OF MANGROVE DAMAGE TO INCOME OF MANGROVE CRAB FISHERMEN AT KELURAHAN BAGAN DELI MEDAN BELAWAN SUBDISTRICT MEDAN CITY NORTH SUMATERA PROVINCE - Rahmaddyanty, Demak; Hendri, Ridar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
This research was conducted in May, 2017 located at Kelurahan Bagan DeliMedan Belawan Subdistrict Medan City North Sumatera Province. This studyaims to determine changes in income generated by mangrove crab fishermenbefore and after the occurrence of mangrove land damage and the efforts ofmangrove crab fishermen to increase income due to damage to mangrove inKelurahan Bagan Deli. The method used in this study is survey method with 36household as respondents detemination by random sampling.The results showed that there was a decrease in income from the catch offishermen of mangrove crabs by IDR 1,702,219.44 per month (54.85%) aftermangrove damage, from IDR 3,103,044.44 to IDR 1,400,825.00 per month andare statistically significant. The efforts of mangrove crab fishermen to increaseincome are diversification of livelihoods, the addition of fishing gear such astraps, fishing rods and nets, mobilizing the role of family members and savingmoney.Keywords: mangrove damage, income, fisherman, mangrove crab